An Estimate of Preventable Harms Associated With Screening Colonoscopy Overuse in the U.S. - Shannon Brownlee, MSc; Alison N. Huffstetler, MD; Joseph Fraiman, MD; Kenneth W. Lin, MD, MPH (AJPM Focus)
Introduction: Screening colonoscopy is often performed on patients who are younger or older than the ages specified in national guidelines or at shorter intervals than recommended. The annual incidence of harms associated with overuse of screening colonoscopy in the U.S. is not known. This study estimated the incidence of low-value screening colonoscopies annually in the U.S. and the number of preventable harms associated with them. Methods: The 2018 National Health Interview Survey was used to estimate the number of annual screening colonoscopies. Rates of colonoscopy overuse and serious (bleeding and bowel perforation) and minor harms were drawn from 3 recent systematic reviews. Results: Approximately 12.4 million screening colonoscopies were completed in the U.S. in 2018. Given the credible range of overuse rates of screening colonoscopy, between 2.1 and 3.2 million low-value colonoscopies occur per year. Applying the credible ranges identified for serious and minor harms secondary to screening colonoscopy resulted in an estimated annual incidence of serious harm from unnecessary colonoscopies ranging from 9,055 to 11,874. The estimate for minor harms ranged from 359,5790 to 1,566,846. Conclusions: In the U.S., screening colonoscopies are often completed at intervals and in populations that are inconsistent with national recommendations, resulting in unnecessary serious and minor harm. Although individual risk is relatively low, the large number of nonindicated screening colonoscopies results in large numbers of adverse events that are preventable with better adherence to recommendations.